Diferenciacija pri poučevanju naravoslovja v prvem in drugem vzgojno-izobraževalnem obdobju osnovne šole - Skribe Dimec, Darja (Revija za elementarno izobraževanje, 2013)
Differentiation in Teaching Science in the First and Second Cycles of Primary Education. There are differences between pupils with regard to their knowledge, but also their abilities or skills and attitudes. The aim of our research study was to determine whether those differences are taken into account while planning and executing primary science lessons. We looked for evidence of differentiation in primary science curricula and textbooks as well as in conceptions and practices of students who are to be future primary school teachers. We noticed that Slovenian curricula designers were clearly aware of the differentiation, as the curricula specifically defined “minimum” and “basic” standards of knowledge. Based on a questionnaire we established that most students were well aware of the differences in pupils’ level of knowledge. An analysis of the lesson plans that were written by students showed significant shortcomings in differentiation in primary science education. As a rule, over 90 per cent of lesson plans that students had to write at the beginning of natural science didactics did not include either quantitative or qualitative differentiation. We found out that once students had completed the teacher education programme, the concept of differentiation was realized through the elements of the constructivist theory of learning. By analyzing various textbooks and workbooks, we tried to determine how the authors of the respective books perceived differentiation. We came to a conclusion that a majority of teaching materials did not incorporate the elements of differentiation.